Comparison of different GnRH compounds on fertility outcomes in ovulation synchronized and presynchronized beef cows - Oosthuizen, Nicola; Goncalves, Lucas M.; Burato, Samir; Smith, Molly S.; Harvey, Kelsey M.; Lamb, Graham Cliff; Fontes, Pedro L. P. (Frontiers in Animal Science, 2025)
This study evaluated the use of two different gonadotropin-releasing hormone (GnRH) compounds in estrus synchronization protocols with or without presynchronization. Cows (n = 1,585) were enrolled in a completely randomized design with a 2×2 factorial arrangement of treatments. Within each location, cows were randomly assigned to one of four treatments: (1 and 2) cows were estrus synchronized using the 7-day CO-Synch + CIDR protocol (7D) wherein they received an injection of one of two GnRH compounds [gonadorelin hydrochloride (GH) or gonadorelin diacetate tetrahydrate (GDT)] and a controlled internal drug release (CIDR) device on day 0, an injection of prostaglandin F2α (PG) at CIDR removal on day 7, and a second injection of their respective GnRH compound at fixed-time artificial insemination (TAI) on day 10 (7D-GH and 7D-GHT); (3 and 4) cows were treated with the 7&7 Synch (7&7) protocol, wherein they were treated the same as treatments 1 and 2 but received their CIDR inserts on day -7 in conjunction with an injection of PG (7&7-GH and 7&7-GDT). Breeding indicator patches were applied to all cows at CIDR removal and were evaluated for activation at TAI. Follicle diameter differed by ovulation synchronization protocol on days 0, 7, and 10, where cows enrolled in the 7&7 had greater (P ≤ 0.008) dominant follicle diameters than those in the 7D. No differences (P ≥ 0.19) in ovarian parameters were determined between GH and GDT cows. Estrus expression differed (P < 0.001) by synchronization protocol and was greater in cows enrolled in the 7&7 than the 7D (80.4 ± 2.8 vs. 55.5 ± 4.1%, respectively), yet no differences (P = 0.32) in estrus expression were determined between GH- and GDT-treated cows. Pregnancy rates to TAI did not differ (P = 0.57) by GnRH compound but differed (P = 0.01) by synchronization protocol, where cows enrolled in the 7&7 had greater PR/AI when compared to those in the 7D (60.9 ± 2.5 vs. 53.9 ± 2.6%, respectively). In conclusion, fertility was improved through the use of presynchronization; however, no differences in fertility parameters were determined between GH and GDT in either synchronized or presynchronized beef cows.